Indonesia’s Prospects As World Class Maritime Power - Setiawan, Rangga; Paschalina, Stella (KnE Social Sciences, 2020)
The possession of Weapons of Mass Destruction (WMD) allows a country to enhance their bargaining position. This approach is coercive rather than peaceful. The idealistic approach using “peaceful” methods to deter the national security threats remains valuable, however, especially for Indonesia as a maritime nation. Indonesia has three factors which obstruct its development as a maritime power. First, there are limited regulations regarding the condition of “secure” regional security in ASEAN. Second, there are limited military funds. Finally, the sea level conditions in the Indonesia waters (known as brown and green sea) are not conducive to naval development. One solution is to leverage the Indonesia Military’s international relations to enhance national maritime power. Keywords: Weapon of Mass Destruction, Maritime Power, Internationalism